The use of free versus in situ right internal mammary artery in coronary artery bypass grafting. Issue 10 (9th July 2021) - Aranda‐Michel, Edgar; Serna‐Gallegos, Derek; Navid, Forozan; Kilic, Arman; Williams, Abraham A.; Garcia, Ricardo; Bianco, Valentino; Brown, James A.; Sultan, Ibrahim
Abstract: Introduction: Coronary artery bypass grafting (CABG) continues to be the most commonly performed cardiac surgical procedure in the world. The use of multiarterial grafting may confer a long‐term survival benefit over the use of vein grafts. However, there is a paucity of data comparing the use of in situ versus free right internal mammary artery (RIMA) in isolated CABG. Methods: Patients that underwent isolated CABG between 2010 and 2018 where RIMA was used in addition to a left internal mammary artery graft. Patients with prior cardiac surgery or percutaneous coronary intervention were excluded. Propensity matching was used for subanalysis. Mortality and major adverse cardiac and cerebrovascular events (MACCE) were analyzed with Kaplan–Meier survival curves and Cox multivariable regression. Heart failure‐specific readmissions were assessed with cumulative incidence curves with Fine and Gray competing risk regression. Results: A total of 667 patients underwent isolated CABG. Of those, 422 had free RIMA and 245 had in situ RIMA utilized. Mortality was similar between cohorts ( p = 0.199) with 5‐year mortality rates of 6.6% (free) and 4.1% (in situ). MACCE was similar between cohorts, with 5‐year event rates of 33.6% and 33.9% ( p = 0.99). RIMA style was not a significant predictor of any outcome. Conclusion: There was no difference in long‐term mortality, complications, MACCE, or heart failure readmissions when comparing a contemporary cohort of patients undergoing isolated CABG utilizing RIMA as a conduit. These data may allow surgeons to consider using RIMA either as an in situ or a free conduit. Abstract :